Aporphine Alkaloids Isolated from the Cardiovascular Active Fraction of Tinospora crispa - N.A, Bakhari; A, Sadikun; T.S, Choon,; T.S, Ying,; M.Z, Asmawi, (Malaysian Journal of Science, 2005)
Preliminary screening using isolated rats' aortic strip and atria showed that the chloroform extract of Tinospora crispa, Miers possessed potent cardiovascular activity. This prompted us to undertake an investigation on the constituents present in CF3 fraction, i.e. the most active fraction of the chloroform extract [1]. Among the chemical constituents isolated from this fraction are aporphine alkaloids, which include two N-acylaporphinoids: N-formylnornuciferine (1) as the major compounds and N-acetylnornuciferine (2), together with a small amount of an oxoaporphine alkaloid; Iysicamine (3). Structural identification of the compounds is based on spectral analysis. Compounds (1) and (2) present as a mixture of Z and E isomers where the ratio of Z/E isomer in each compound are 1.7/1.0 and 1.3/1.0 respectively, based on the intensity of the signal for one proton in Ã‚Â¹H-NMR spectrum. Isolation of (3) is reported the first time in Tinospora genus.